Fracture reasons in ceramic-fused-to-metal restorations - (:unkn) unknown (WILEY, 2003)
Ceramic-fused-to-metal restorations are widely used in dentistry with a high degree of general success. Fracture of the ceramic veneers as a result of oral function or trauma is not an uncommon problem in clinical practice. Although fractures of such restorations do not necessarily mean the failure of the restoration, the renewal process is both costly and time consuming and therefore remains a clinical problem. Fractures in the anterior region pose an aesthetic problem but when they are in the posterior, chewing function could also be affected. The published literature reveals that reasons for failures cover a wide spectrum from iatrogenic factors to laboratory mistakes or because of factors related to the inherent structure of the ceramics or simply to trauma.
Keywords: fracture; ceramics; PORCELAIN REPAIR MATERIALS; STRESS; STRENGTHS; FAILURES; FATIGUE; BRIDGES; CROWNS